Validation and clinical application of a method to quantify nevirapine in dried blood spots and dried breast milk spots - Olagunju, Adeniyi (J Antimicrob Chemother, 2015)
OBJECTIVES: The validation and clinical application of a LC-MS/MS method for the quantification of nevirapine in dried blood spots (DBS) and dried breast milk spots (DBMS) are presented. METHODS: DBS and DBMS were prepared from 50 and 30 µL of nevirapine-spiked whole blood and human breast milk, respectively. Chromatographic separation was achieved on a reverse phase C18 column with 0.1% formic acid in water/acetonitrile using a solvent gradient program at a flow rate of 400 µL/min and detection was by TSQ Quantum Access triple quadrupole mass spectrometer. The clinical application was evaluated in HIV positive nursing mothers and their breastfed infants. RESULTS: The assay was validated over the concentration range of 50-10000 ng/mL. Accuracy ranged from 93.3 to 113.4% and precision ranged from 1.9 to 12.0%. The mean (percentage coefficient of variation, %CV) recovery of nevirapine from DBS and DBMS was ≥70.7% (≤8.2) and matrix effect was ≤1.04 (≤6.1). Nevirapine was stable in DBS and DBMS for ≥ 15 months at room temperature and -80°C. Mean (SD) AUC(0-12), C(max) and C(min) in maternal plasma versus breast milk were 57808 ng.h/mL (24315) versus 55817 ng.h/mL (22368), 6140 ng/mL (2605) versus 5231 ng/mL (2215) and 4334 ng/mL (1880) versus 4342 ng/mL (2245), respectively. The milk-to-plasma concentration ratio over the dosing interval was 0.94 (0.15). Infant plasma concentrations 2 and 8 hours after maternal dose were 580.6 ng/mL (464.7-1607) and 584.1 ng/mL (381.5-1570), respectively. CONCLUSIONS: These methods further extend opportunities for conducting clinical pharmacokinetic studies in nursing mother-infant pairs, especially in resource-limited settings.